Synthesis of biopetrol from rubber seed oil using zeolite catalyst using cracking process - Mohamed Fareez, Jafri (2012)
The rubber seeds oil are readily available, cheap and help to improve the socioeconomic issues it is also easy to abtain because Malaysia is a biggest country that produce natural rubber. The rubber seed oil is extracted using the Soxhlet Extraction method. The cleaned, shelled and milled rubber seeds are placed into a thimble in the main chamber of the extractor. The solvent in the receiving flask is left to boil until it vaporizes and condensed, filling up the main chamber, extracting the RSO from the rubber seeds. The catalytic cracking of the mixture of 25mL of RSO, using variable mass of zeolite catalyst that is 1 grams, 2.5 grams , 5 grams and 10 grams of catalyst first been weighed after and before the cracking. At 300 0C the furnace has been set up to 15 minutes using zeolite catalyst is to boost up the rate of reaction so that more successful reactions between the reactant particles can occur. The presence of Isooctane in a sample detected using Gas Chromatogram indicating that bio-petrol can be produced. Standards of different ratio mixtures of hexane and Isooctane were used to obtain chromatograms for Isooctane until a calibration curve is plotted from which the Isooctane produced can be determined. The results show that the actual concentration of Isooctane is very big. This could be explained using the cause of interlayer spacing of catalyst structure, larger surface area for reactions to occur, various types of fatty acid mixture present in rubber seed oil, the incorrect chromatogram modifications and the contamination in rubber seed oil. The mass of catalyst, volume or dilution factor of rubber seed oil, temperature of the cracking process used will affect the percentage of concentration of Isooctane in samples. As a conclusion, Bio-petrol can be produced from rubber seed oil using zeolite catalyst in the catalytic cracking process. And if the mass of catalyst increase it will increase the concentration of isooctane produced.